Global health educational trips: ethical, equitable, environmental? - Velin, Lotta; van Daalen, Kim; Guinto, Renzo R *; van Wees, Sibylle Herzig; Saha, Senjuti (BMJ Publishing Group, 2022)
Global health education in medical schools and at premedical undergraduate levels in high-income countries is often limited to short courses aimed at introducing students to the topic. These courses frequently include or focus on trips to low and middle-income countries, so the students can ‘experience global health’. There are several problems with this type of learning experience. To begin with, this form of ‘global health tourism’ can be traced back to ‘tropical medicine’—a field plagued by paternalism and asymmetric power dynamics, where the so-called ‘Global North’ dominated the discourse at the expense of the ‘Global South’. Such ‘global health tourism’ supports the frequent misinterpretation of global health as ‘health abroad”.